Bidder Participation and Information in Currency Auctions - Romeu, Rafael (IMF Working Papers; Working Paper ;, 2005)
This paper studies the participation and performance of sophisticated versus unsophisticated auction participants in an environment with numerous bidders, uncertainty, and asymmetric information. We examine multi-unit, pay-as-bid, currency auctions conducted by the Central Bank of Venezuela. We find that sophisticated bidders outperform their less sophisticated rivals during periods of high volatility, apparently as a result of their superior informationgathering ability. The result is consistent across both quantity (sophisticated bidders win more market share) and price (sophisticated bidders pay lower premiums). The result is consistent with the view that a pay-as-bid auction format may be detrimental to participation by less-informed bidders.